Balance of Transient Thermal Energy on the Forced Flow Rotary dryer - Ricki Murti, Made (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010, 2012)
There have been many studies about the dryer with a static bed so dry material produced is not uniform. Thus, drying withrotating bed can produce the dry material uniformly. Usually a prototype closest to the efficiency of the system as aperformance, but it has not been able to show its thermal energy balance. So the target of this research is a transient thermalenergy balance. Data taken in the testing include: the temperature inlet fluid of drying chamber channel (Tin), the velocity offluid flow into drying chamber channel (V), the outlet fluid temperature from drying chamber channel (Tout), the temperatureof dried material (Tmtl), the mass of dried material (mmtl), the surface temperature in the drying chamber wall (Tdlm), surfacetemperature out the drying chamber wall (Tluar). Next step is to get the results of data processing in the form of transientthermal energy balance in tables and graphs. From the results it can be seen that the useful energy decreases with timealthough the incoming energy drying system increased slightly. From the energy balance of thermal performance is obtainedalso in the form of thermal efficiency and average thermal efficiency is 18%. Decrease in useful energy as a function of time,causes the thermal efficiency as a function of time was also decreased, it is characterized by a decrease in the mass ofmaterial because the condition is getting dry.
Keywords: the rate of incoming energy, the total rate of energy losses, the rate of evaporation energy, the rate of saved energy change.